Potency of sponge-associated bacteria producing bioactive compounds as biological control of vibriosis on shrimp - Rini, Adityawati Fajar; Yuhana, Munti; Wahyudi, Aris Tri (Jurnal Akuakultur Indonesia, 2017)
ABSTRACT The aims of this study were to obtain sponge-associated bacteria as biocontrol to inhibit vibriosis in vitro and in vivo, to identify the bacterial isolates based on 16S-rRNA gene, and to detect the presence of nonribosomal peptide synthetase (NRPS), and polyketide synthase (PKS) genes to prove its ability of bioactive compounds synthesis. Aaptos sp. and Hyrtios sp. sponges were collected from Pramuka Island, Jakarta. The isolation using sea water complete (SWC) and  zobel marine agar (ZMA) medium obtained 174 isolates. A total 69 isolates were screened successfully based on their antibacterial activity. 47 isolates showed negative haemolysis through hemolytic assays. The pathogenicity test used twelve selected isolates that have a broad spectrum of antibacterial activity and haemolysis negative. The result of pathogenicity test showed  that 12 isolates were not pathogenic to the shrimp post larvae with no significantly different (P>0.05) between treatment and negative control. Results of challenge test with Vibrio harveyi have a significant difference survival (70±5.0–90±0.0%) (P<0.05) compared with positive control (38.3±2.9%). Genetic analysis based on 16S-rRNA revealed the groups of three genera belonged to Pseudomonas, Staphylococcus, and Alcaligenes. Based on amplification of NRPS and PKS genes, four bacterial isolates have been detected to have only NRPS gene, one isolate has only PKS, and one isolate has both genes. The results indicate that the potency of six sponge-associated bacteria as bioactive compounds producers. Keywords: NRPS, PKS, anti-vibriosis, Pacific white shrimp  ABSTRAK Penelitian ini bertujuan untuk memperoleh isolat bakteri asosiasi spons yang mempunyai kemampuan dalam menghambat vibriosis secara in vitro, in vivo dan mendeteksi gen 16S-rRNA, nonribosomal peptide synthase (NRPS) serta polyketide synthase (PKS) untuk memastikan kemampuan mensintesis senyawa bioaktif. Spons Aaptos sp. dan Hyrtios sp. berhasil dikoleksi dari perairan Pulau Pramuka, Kep. Seribu Jakarta. Isolasi bakteri dengan menggunakan media sea water complete (SWC) dan zobel marine agar (ZMA) diperoleh 174 isolat. Sebanyak 69 isolat terdeteksi memiliki aktivitas antibakteri. Uji hemolisis menunjukkan 47 isolat adalah hemolisis negatif. Uji patogenisitas menggunakan 12 isolat terpilih yang memiliki spektrum luas dan hemolisis negatif. Hasil uji patogenisitas tehadap 12 isolat menunjukkan bahwa semua isolat tidak bersifat patogen terhadap pascalarva udang vaname. Hal ini dibuktikan dengan sintasan pascalarva udang vaname yang tidak berbeda nyata (P>0,05) dengan kontrol negatif. Hasil uji tantang terhadap Vibrio harveyi diketahui sintasan pascalarva udang vaname (70±5,0–90±0,0%) memiliki perbedaan yang signifikan jika dibandingkan dengan kontrol positif (38,3±2,9%). Berdasarkan analisis sekuen gen 16S-rRNA, menunjukkan bahwa isolat-isolat tersebut memiliki kemiripan dengan genus Pseudomonas, Staphylococcus, dan Alcaligenes. Deteksi gen NRPS dan PKS menggunakan PCR diperoleh  empat  isolat bakteri memiliki hanya gen NRPS, satu isolat memiliki hanya gen PKS, dan satu  isolat memiliki kedua gen NRPS-PKS. Hal ini membuktikan bahwa  keenam isolat memiliki potensi sebagai penghasil senyawa bioaktif.   Kata kunci: NRPS, PKS, antivibriosis, udang vaname